Blends: an intermediate category at the crossroads of morphology and phonology - Hamans, Camiel (Yearbook of the Poznan Linguistic Meeting, 2021)
Blends are traditionally seen as irregular and unsystematic. In this paper it is shown that one must make a distinction between stub compounds or clipped compounds (sitcom, misper) and real blends (brunch, advertorial). In much of the literature on blends, however, stub compounds are classified as blends. Stub compounds appear to be compounds and follow the Compound Stress Rule, whereas blends turn out to form a category of its own. Blends exhibit a right-hand head and insofar they can be compared to compounds. However, their prosodic structure is a copy of the second source word, the word where the final part of the word comes from. The analysis presented here demonstrates that blends consist of one prosodic word, whereas compounds consist of two. This proves that blends are an intermediate category of their own at the intersection of phonology and morphology. The examples discussed mainly come from English. Data from Dutch and German is also presented.